Preliminary In Vitro Evaluation of Genistein Chemopreventive Capacity as a Result of Esterification and Cyclodextrin Encapsulation. (26th May 2015) - Danciu, Corina; Soica, Codruta; Dehelean, Cristina; Zupko, Istvan; Csanyi, Erzsebet; Pinzaru, Iulia
Abstract : The present study focuses on the synthesis and analysis of a genistein ester derivative with myristic acid followed by beta cyclodextrin encapsulation; physicochemical analysis using consecrated techniques such as FTIR, MS, DSC, and SEM revealed both a successful esterification and inclusion inside the cyclodextrin cavity. Cytotoxic effects were measured in vitro on three human cell lines: HeLa (cervix adenocarcinoma), A2780 (ovary carcinoma), and A431 (skin epidermoid carcinoma). The in vitro biological analysis exhibited rather poor antiproliferative results on all three tested cancer cell lines, behavior that may be due to the high stability of the complex within the in vitro environment.